SPECTRUM OF CONGENITAL HEART DISEASE DIAGNOSED BY ECHOCARDIOGRAPHY EVALUATION IN NEONATES PRESENTING TO TERTIARY CARE HOSPITAL - KHAN , I; AYESHA, .; MUHAMMAD , A (Biological and Clinical Sciences Research Journal, 2024)
Neonatal morbidity and mortality are significantly impacted by congenital heart disease (CHD). Echocardiography plays a crucial role in this condition's early diagnosis and management. This research aims to determine the prevalence of CHD diagnosed by echocardiography among neonates admitted to Lady Reading Hospital (LRH), Peshawar. Objective: To identify the rate and variety of CHD in neonates using echocardiography. Methods: A prospective study was conducted in the Department of Pediatrics at LRH Peshawar from January 2023 to January 2024. The study included 100 neonates up to 28 days old with clinical manifestations of CHD. Routine echocardiographic examinations were performed for diagnosis. Descriptive statistics were used to determine the prevalence and type of CHD, while inferential statistics compared means, standard deviations, and p-values. Results: Out of 100 neonates, 72 were diagnosed with CHD. The mean age was 15 days (± 7 days). The most frequently reported defect was ventricular septal defect (VSD), observed in 35% of cases. Atrial septal defects (ASD) were seen in 20% of cases, tetralogy of Fallot (TOF) in 10%, and transposition of the great arteries (TGA) in 8%. The p-value for the prevalence of CHD in males compared to females was 0.03, indicating a significant difference. Conclusion: CHD is relatively frequent in neonates, and neonatal echocardiography is a valuable tool for early diagnosis. Early detection allows for timely management, improving prognosis in affected infants.